2018
DOI: 10.3389/fimmu.2018.02036
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Stimuli Induce PAD4-Dependent, ROS-Independent NETosis, With Early and Late Events Controlled by Discrete Signaling Pathways

Abstract: Neutrophils are known to extrude decondensed chromatin, thus forming NETs (neutrophil extracellular traps). These structures immobilize pathogens, thereby preventing their spreading, and are also adorned with antimicrobial molecules. NETs can also influence pathogenesis in chronic inflammation, autoimmunity, and cancer. Despite the importance of NETs, the molecular mechanisms underlying their formation, as well as the upstream signaling pathways involved, are only partially understood. Likewise, current method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
134
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(146 citation statements)
references
References 63 publications
10
134
2
Order By: Relevance
“…PAD4 is an important mediator of innate immunity since PAD4 -/mice were shown to be more vulnerable to bacterial infection (34). Moreover, it was recently shown that many known physiological NET inducers (N-Formylmethionyl-leucyl-phenylalanine [fMLP], GM-CSF, TNFα, or PMA) are PAD4 dependent (35). Here again, we found that PAD4 -/-TBM had significantly lower NET levels compared with untreated TBM ( Figure 2D).…”
Section: Resultssupporting
confidence: 62%
“…PAD4 is an important mediator of innate immunity since PAD4 -/mice were shown to be more vulnerable to bacterial infection (34). Moreover, it was recently shown that many known physiological NET inducers (N-Formylmethionyl-leucyl-phenylalanine [fMLP], GM-CSF, TNFα, or PMA) are PAD4 dependent (35). Here again, we found that PAD4 -/-TBM had significantly lower NET levels compared with untreated TBM ( Figure 2D).…”
Section: Resultssupporting
confidence: 62%
“…In view of the prevalence of gouty arthritis and of the neutrophil involvement in its pathogenesis, a better understanding of both MSU-elicited responses and of their molecular bases is clearly needed. In this regard, our previous work has provided several potential clues, insofar as we have shown the crucial involvement of TAK1, MAPKs, PI3K, and Syk in cytokine generation, delayed apoptosis, and NETosis in response to several physiological neutrophil stimuli (23)(24)(25)(26)(27). Under the same stimulatory conditions, we have also established that several transcription factors (e.g., NF-κB, C/EBP, CREB) drive cytokine production in neutrophils (23,26,28,29).…”
Section: Introductionsupporting
confidence: 52%
“…Conversely, our finding that MSU-induced NET formation depends on PAD4, is to our knowledge a first. Thus, MSU appears to function like most other physiological neutrophil agonists (e.g., TNFα, GM-CSF, fMLP, PAF, C5a, CXCL8) with respect to the involvement of endogenous ROS and PAD4 (27). Overall, our findings substantially extend our understanding of the mechanisms underlying NET generation, by showing that MSU crystals represent yet another class of physiological stimuli (in addition to growth factors, chemoattractants, and cytokines) (27) that employ common signaling components, as well as PAD4.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This may in part be explained by the fact that neutrophils were shown to produce NETs in response to high quantities of invading pathogens and their virulence factors (DAMPs or PAMPs) (Papayannopoulos, 2018) or pathogens too large to be cleared by phagocytosis alone (Branzk et al, 2014). However, recent evidence also suggests that NET formation can occur independently of MPO and NOx (Kenny et al, 2017) and ROS (Pilsczek et al, 2010;Tatsiy & McDonald, 2018). The relative importance of these different NET production pathways remains debated.…”
Section: A Convergent Immune Role For Trap Components In Root Bormentioning
confidence: 99%